Narratives about a mestizo territory: racial mixtures of Brazil in the perspective of three foreigners in the nineteenth century (Saint-Hilaire, Louis Agassiz and Louis Couty) - Giarola, Flávio Raimundo (Revista Crítica Histórica, 2020)
During the nineteenth century, several foreigners toured Brazil with diverse objectives, ranging from diplomatic missions to scientific expeditions that sought to recognize the biological and geographical diversity of the region. On these excursions, travelers also made descriptions of the populations they encountered along the way and developed theses on the development potential of a mixed-race territory with a considerable number of blacks. Thus, our article analyzes the representations about the mestizo and the mestizaje in the travel accounts and in the observations of three foreigners who were in Brazil at different times of the nineteenth: Auguste de Saint-Hilaire, Louis Agassiz and Louis Couty. We argue that the foreign narratives about the racial mix and about the consequences of these mixtures for Brazil suffered little change over the period analyzed, since they were fundamentally driven by the predominant European racialism in the sciences of that century.